Polarization Splitter-Rotator Based on Multimode Waveguide Grating - Yannong Luo; Renyou Ge; Haozhi Luo; Meiyan Wu; Lidan Zhou; Makunda Aryal; Wenwei Li; Jianhui Yuan; Jian Xu; Quanxue Lan; Yongqing Li; Xinlun Cai (Crystals, 2021)
We demonstrate a polarization splitter rotator (PSR) based on multimode waveguide grating (MWG) on a silicon-on-insulator (SOI) platform. Bloch mode hybridization in mini-stopband is exploited to achieve high polarization conversion efficiency. The fabricated device yields a high extinction ratio of > 53 dB and > 31 dB, low crosstalk of < −26.4 dB and < −40 dB for the injected TE0 and TM0 mode, with average insertion loss of 1.2 dB and 1.5 dB in the wavelength regime 1552 nm–1562 nm. Such a device shows great design flexibility and an easy fabrication process, serving as a good candidate in integrated polarization diversity circuits, especially for applications requiring spectra manipulation. Additionally, the polarization conversion approach provides opportunities to develop novel polarization management devices.